(untitled) (Jurnal Ilmiah Teknik Sipil, 2026)
Construction activities in the oil and gas industry are inherently associated with a high level of occupational safety and health risks. Field-related factors that influence workers’ safety perceptions are therefore critical to be identified in order to ensure the effective implementation of safe work behaviors. This study aims to analyze the relationship between mental stress and organizational relationships and their effects on safety perception among field workers in the oil and gas industry, particularly within the operational area of Riau Province, Indonesia. The respondents consisted of 106 field workers, and a quantitative research approach was employed. Data were analyzed using multiple linear regression analysis. The results indicate that mental stress and organizational relationships have a significant influence on workers’ safety perceptions, with a combined explanatory contribution of 39.6%. Higher levels of mental stress tend to increase workers’ negligence and reduce their concern for safety perception. Conversely, stronger organizational relationships enhance workers’ understanding and awareness of safety perception, which in turn contributes to the reduction of workplace accidents.